The relative age effect in the 10 best leagues of male professional football of the Union of European Football Associations (UEFA) - Yagüe, J. M.; de la Rubia, A.; Sánchez-Molina, J.; Maroto-Izquierdo, S.; Molinero, O. (Journal of Sports Science & Medicine, 2018)
The aim of the present research was to observe the relative age effect on professional soccer players of the ten best leagues of the Union of European Football Associations (UEFA), according to the IFFHS (International Federation of Football History and Statistics). The sample consisted of 5201 professional players who participated in the professional leagues during the 2016-2017 season. The birth date of each player was classified in four quartiles (Q1, Q2, Q3 and Q4). The frequencies (fr) and percentages (%) of the birth quartiles were analyzed. The chi square test (X2) and degrees of freedom (gl) were performed to check the differences in the intergroup distribution. Likewise, odd ratios were calculated for the different quartiles, where Q4 was the reference group according to the different leagues studied, playing positions (goalkeeper, defender, midfielder and forward) and classification (first four places, half-of the table and four last places). To calculate the size of the effect on the nominal variables, the Cramer V test was carried out. The results confirmed a greater representation of players born in Q1 and Q2, indicating statistically significant values (p < 0.05) for all the leagues studied, except in the Eerste Klasse A (Belgium). This significance was repeated for the demarcation variables in the field, with a greater effect in the case of the midfielders. Finally, the RAE also affected the three groups according to teams´ classification. The conclusions confirm the effect of the RAE in the sample studied, which would require a review of the talent selection processes in football in order to balance the chances of success of players born at the end of the year.